2012
DOI: 10.1159/000338232
|View full text |Cite
|
Sign up to set email alerts
|

DAD-6: A 6-ltem Version of the Disability Assessment for Dementia Scale Which May Differentiate Alzheimer’s Disease and Mild Cognitive Impairment from Controls

Abstract: Background: The need to detect early changes in instrumental activities of daily life led us to modify the Disability Assessment for Dementia Scale (DAD) by focusing on executive components of 6 instrumental items (DAD-6). Aim: To evaluate the relevance of the DAD-6 for detecting early impairment in a nondemented population. Methods: The DAD-6 was administered to informants of 84 patients: 31 with mild dementia (MD), 53 with mild cognitive impairment (MCI) and 55 healthy controls. Results: DAD-6 scores gradual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 29 publications
1
21
0
1
Order By: Relevance
“…[ 2 ] was reported without specific cutoff values or with a combination of Petersen and Winblad criteria. Mean Mini Mental State Examination (MMSE) [ 35 ] scores ranged from 23.1 [ 36 ] to 28.7 points [ 37 ] for MCI samples, from 26.5 [ 36 ] to 29.4 points [ 30 , 38 ] for normal control samples and from 16.4 [ 39 ] to 25.5 points [ 40 ] for Alzheimer’s disease (AD) samples. In each examined study, however, the MMSE score for the MCI group was lower than that for the comparative control group and higher than that for the dementia sample.…”
Section: Resultsmentioning
confidence: 99%
“…[ 2 ] was reported without specific cutoff values or with a combination of Petersen and Winblad criteria. Mean Mini Mental State Examination (MMSE) [ 35 ] scores ranged from 23.1 [ 36 ] to 28.7 points [ 37 ] for MCI samples, from 26.5 [ 36 ] to 29.4 points [ 30 , 38 ] for normal control samples and from 16.4 [ 39 ] to 25.5 points [ 40 ] for Alzheimer’s disease (AD) samples. In each examined study, however, the MMSE score for the MCI group was lower than that for the comparative control group and higher than that for the dementia sample.…”
Section: Resultsmentioning
confidence: 99%
“…However, the studies investigating the needs in relation to robot use to support older adults with mild cognitive impairment (MCI) are sparse. MCI is associated with impairments in complex instrumental activities of daily living (IADL), for example, finances and medication management, which are dependent on memory and executive functioning (de Rotrou et al, 2012;Schmitter-Edgecombe, Woo, & Greeley, 2009;Yeh et al, 2011). It was suggested that individuals with MCI have the potential to benefit from technologies that would assist them with IADL completion.…”
mentioning
confidence: 99%
“…Le souci d'améliorer ce diagnostic précoce a été à l'origine d'un travail sur la DAD, qui a consisté en la validation d'une version abrégée : la DAD-6 [25]. Les résultats de la validation de la DAD-6 étant publiés, nous n'en donnons ici qu'un bref résumé.…”
Section: Dad-6 : Version Abrégée De La Dad (Disability Assessment Forunclassified